Contribution to the study of the Ria de Aveiro inlet morphodynamics - Plecha, Sandra Marta Nobre (2011)
Over the years it was observed at the Ria de Aveiro lagoon inlet, near the head of the north breakwater, a depth increase that might threaten the stability of this structure. A trend of accretion in the navigation channel of this lagoon is observed, endangering the navigation in this region. In order to understand the origin of these and other trends observed, the knowledge of the sediment transport in the study area is imperative. The main aim of this work is understanding the dominant physical processes in the sediment transport of sediment at the Ria de Aveiro lagoon inlet and adjacent area, improving knowledge of this region morphodynamics. The methodology followed in this study consisted in the analyzes of the topohydrographic surveys performed by the Administration of the Aveiro Harbor, and in the numerical simulations results performed with the morphodynamic modeling system MORSYS2D. The analysis of the surveys was performed by studying the temporal evolution of the bathymetry. The numerical analysis was based on the implementation of the model at the study area, sensitivity analysis of the formulations used to compute the sediment transport to the variation of input parameters (e.g. depth, sediment size, tidal currents) and analysis of the sediment uxes and bathymetric changes predicted. The simulations considered as sediment transport forcing the tidal currents only and the coupled forcing of tides and waves. Considering the wave e ect as sediment transport forcing, both monochromatic waves and a wave regime were simulated. The results revealed that the observed residual sediment transport patterns are generated due to the channel con guration. Inside the lagoon the uxes are mainly induced by the tidal currents action, restricting the action of waves to the inlet and adjacent coast. In the navigation channel the residual sediment uxes predicted are directed o - shore with values between 7 and 40 m3=day generating accretions of approximately 10 m3=day for the shallower region and 35 m3=day for the region between the tidal gauge and the tri^angulo das mar es. At the inlet, the residual uxes are approximately 30 m3=day inducing trends of erosion of approximately 20 m3=day. At the North side of the nearshore accretion is predicted, while at the South side is predicted erosion, at the rates of 250 and 1500 m3=day, respectively. It was also concluded that the waves with higher contribution to the residual sediment uxes are those with heights between 4 and 5 m. However, the storm waves with heights bigger than 5 m, despite their 10% of frequency of occurrence are responsible for 25% of the observed sediment transport.